Deixis Analysis on Joe Biden’s Speech “Remarks on Afghanistan” - Nidaan Khofiyaa; Pininta Veronika Silalahi (Anaphora : Journal of Language, Literary, and Cultural Studies, 2022)
In communication, a speaker sometime uses language features which to point or indicate objects, places, persons, times, and text passages in a specific context. This language features are called deixis or deictic expression. The aim of this study is to find out and describe what kind of deixis and reference used by Joe Biden in his speech. In conducting the study, the researcher conducts the descriptive qualitative method because the result and discussion of this study is presented in a word and descriptive form and focused on quality of the researcher’s interpretation. This study applied the classification of deixis by Stephen C. Levinson (1983). There are 203 words of person deixis, 54 data of place deixis, 45 data of time deixis, 12 data of social deixis, and 31 data od discourse deixis. The result show that person deixis is mostly use by Joe Biden in his speech. This implies that the speech is considered as important so that the speaker express himself as the president as the center of the speech. The result show that the speech by Joe Biden is not only contains of deixis, but it also contains of reference. The result show that there are two types of reference in Joe Biden’s speech, namely Personal reference and demonstrative reference. This study also applied the theory of reference by Halliday and Hasan (1976). This implies that the speech is not only attract people to understand of what, who, when, and where the speaker means, but the speech is also considered as a text and meaningful.